The Genus Sulettaria A.D.Poulsen & Mathisen (Zingiberaceae) in Sarawak, Malaysia - Meekiong, Kalu; Glathycthia, Andrian; Stephen, Teo Ping; Jovita, Eldeson Ripen; Salasiah, Mohamad (UTHM Publisher, 2023)
Zingiberaceae is one of the most common herbaceous plant families in the tropical rainforests of Borneo, Malaysia. Many studies have been conducted on this family, yet the documentation of this family is still far from complete. Zingiberaceae also included many species that were reclassified, with many new genera introduced to accommodate the species based on the molecular work. Sulettaria A.D.Poulsen and Mathisen is one of the examples of a new genus introduced to accommodate such ginger species from Southeast Asia formerly from the genera Elettaria and Amomum. The majority of the species that are assigned to this new genus are found in Sarawak. This study aims to document information on Sulettaria with special reference to ecological and taxonomic aspects from Sarawak. A checklist of species found in Sarawak is included. Keywords: Borneo, diversity, endemic, Malaysia, taxonomy, wild gingers